(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2023)
Rural areas of Samarkand, which have a rich historical and cultural heritage, face problems in the field of economic and social development. As an innovative form of tourism, agritourism is a promising tool for promoting sustainable rural development. This brief provides an overview of the main aspects of rural development in Samarkand from an agritourism perspective. Finally, the article examines the challenges and prospects for agritourism development in Samarkand and offers practical recommendations for public and private stakeholders, as well as the academic community, to promote sustainable rural development through agritourism in the region.